2019
DOI: 10.1002/ijgo.12985
|View full text |Cite
|
Sign up to set email alerts
|

Disability and functioning of women with low‐risk pregnancy: Assessment using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0)

Abstract: Objective To evaluate the disability and functioning of women with low‐risk pregnancy in the second and third gestational trimesters. Methods A longitudinal observational study was conducted from June 5, 2015, to April 30, 2016, in Family Health Units in the city of Santa Cruz, Rio Grande do Norte, Brazil, involving women who were in the second trimester of pregnancy where the pregnancy had been classified as low‐risk. A form was designed specifically for the study to collect sociodemographic, urogynecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Functional status describes a person’s ability to perform a task or activity in the environment in which they live and is the result of a dynamic interaction between health conditions and contextual factors, integrating the different dimensions of health (individual, biological and social) 11 12. Functional status after childbirth is defined as mother’s ability to resume self-care, household, social, community, occupational and infant care activities 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Functional status describes a person’s ability to perform a task or activity in the environment in which they live and is the result of a dynamic interaction between health conditions and contextual factors, integrating the different dimensions of health (individual, biological and social) 11 12. Functional status after childbirth is defined as mother’s ability to resume self-care, household, social, community, occupational and infant care activities 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, using WHODAS, of disability in women, have been reported in the following areas: oncology [ 12 15 ], obstetrics [ 16 18 ], urology [ 19 , 20 ] and sexual function [ 21 ]. These studies underscore the importance of understanding women’s health contexts using the ICF; as well as, understand the impact of women’s health problems on their activities and participation, through a comprehensive and standardized instrument.…”
Section: Introductionmentioning
confidence: 99%
“…22,36 Pregnancy-related pain has been associated with disruptions to activities of daily living, including but not limited to physical activity, hygiene, and work-related functioning. 6,14 This can lead to feelings of dependence and inadequacy, as well as a loss of personal identity, because unmanaged pain may require women to take premature leave from work, affect their sexual relationship with their partner, and/or make it difficult to engage in selfcare. 6,14 Pain interference, or the extent to which pain affects an individual's activities of daily living, is thus an important consideration in understanding pain experience.…”
Section: Introductionmentioning
confidence: 99%
“…6,14 This can lead to feelings of dependence and inadequacy, as well as a loss of personal identity, because unmanaged pain may require women to take premature leave from work, affect their sexual relationship with their partner, and/or make it difficult to engage in selfcare. 6,14 Pain interference, or the extent to which pain affects an individual's activities of daily living, is thus an important consideration in understanding pain experience. 2 Pain during pregnancy has been strongly associated with psychological distress, including pain catastrophizing, which is the tendency to ruminate, magnify, or feel helpless in the presence of pain.…”
Section: Introductionmentioning
confidence: 99%